Effects of pharmacology with acepromazine maleate in tranquilization, hematology and vital parameters in cats - Tannus, L. F.; Eurides, D.; Mundim, E. D.; Mundim, V. A.; Eurides, G. P.; Vieira, R. B. K. (Scientific Electronic Archives, 2015)
This work aims to evaluate the tranquilization, the hematological and the physiological parameters of domestic cats undergoing pharmacupuncture with acepromazine maleate. Seven animals received 5% of the dose of the drug indicated for this species in acupoint Yintang (GI) and seven (GII) received the same dose intramuscularly. The reassurance was assessed using a scale adapted from Dobbins et al. (2002). The GI group demonstrated that 71.43% of the animals presented drowsiness and projection of the third eyelid and 28.47% were less active. In GII group, 14.28% of cats were less active and 85.72% demonstrated were unchanged. About the hematologicals changing, the two groups demonstrated a slight increase of leukocytes, in GI decreased hematocrit and erythrocytes. According to physiological parameters, GI presented decrease rectal temperature and increase in respiratory rate. There were no significant changes on the heart rate and systolic blood pressure in any cat. In GII, occurred a decrease in diastolic blood pressure. The pharmacupunture showed effectiveness in cats tranquilization, besides clinical safety.